Can a franchise chain coordinate? - Michael, Steven C (Journal of Business Venturing, 2002)
In today's business landscape, the familiar traditional corporation has been augmented by new species, such as joint ventures, strategic alliances, and franchise chains. The properties of these new species, termed hybrid forms, are distinctly different from the traditional corporation. In this paper, we examine whether one hybrid form, the franchise chain, can coordinate elements of the marketing mix (price, quality, and advertising) in the pattern suggested by theory and achieved by the traditional corporation. Results suggest they cannot. Therefore, franchise chains appear to be unable to coordinate the elements of the marketing mix. Implications for theory and practice are discussed.